Dissemination of Klebsiella pneumoniae ST147 NDM-1 in Poland, 2015–19. (24th June 2021) - Biedrzycka, M; Urbanowicz, P; Guzek, A; Brisse, S; Gniadkowski, M; Izdebski, R
Abstract: Objectives: To assess the spread of New Delhi metallo-β-lactamase-1 (NDM-1)-producing Klebsiella pneumoniae ST147 organisms in Poland since an introduction from Tunisia in March 2015, including their phylogenetic position in the global population of the high-risk clone. Methods: Out of 8925 unique NDM-positive K. pneumoniae isolates identified in Poland from April 2015 till December 2019, 126 isolates, including the Tunisian imports, were related by PFGE and bla NDM gene-carrying Tn 125 transposon derivatives. Forty-seven representative isolates were sequenced by Illumina MiSeq. The phylogeny, resistome, virulome and plasmid replicons were analysed and compared with the international ST147 strains. Plasmids of six isolates were studied by the MinION sequencing. Results: A high homogeneity of the 47 isolates was observed, with minor variations in their resistomes and plasmid replicon profiles. However, the detailed SNP comparison discerned a strict outbreak cluster of 40 isolates. All of the organisms were grouped within the ST147 phylogenetic international lineage, and four NDM-1 producers from Tunisia, Egypt and France were the closest relatives of the Polish isolates. Yersiniabactin genes (YbST280 type) were located within the ICE Kpn12 -like element in most of the outbreak isolates, characterized by O2v1 and KL64 antigen loci. The bla NDM-1 genes were located in double-replicon IncFIIK2 +IncFIBK plasmids. Conclusions: The continuous spread of K. pneumoniae ST147 NDM-1 in Poland since 2015, largely in the Warsaw area, is demonstrated by this genomic analysis. The isolates showed a high degree of homogeneity, and close relatedness to organisms spreading in the Mediterranean region.